Graphite in ureilites, enstatite chondrites, and unique clasts in ordinary chondrites: insights from the carbon-isotope composition - Storz, Jakob; Ludwig, Thomas; Bischoff, Addi; Schwarz, Winfried H.; Trieloff, Mario (Geochimica et cosmochimica acta, 2021)
Carbon is of fundamental interest for constraining the volatile element inventory of terrestrial planets. In some meteorites, like ureilites and enstatite chondrites, graphite is the major carbon-carrier. Here, we report the in-situ analyses of graphite in 19 ureilites, 11 enstatite chondrites, and 3 graphite-bearing clasts in ordinary chondrites by secondary ion mass spectrometry (SIMS). In coarse-grained ureilites the obtained carbon-compositions of graphite range from -9.2‰ to -0.1‰ (δ13C). The carbon-composition tends to be homogeneous within a sample and correlates with the Fa content in olivine. In contrast, fine-grained ureilites exhibit considerable intra-sample heterogeneity, and graphite tends towards 13C-enriched compositions (up to +10.4‰). Isotopic and petrographic differences are presumably a result of post-igneous shock processing, including annealing during impact smelting. Enstatite chondrites host a variety of graphite morphologies, occurring in two distinct assemblages: Silicate-associated graphite (SAG) and metal-associated graphite (MAG). These assemblages show diverging carbon-compositions: SAG consistently exhibits δ13C in a narrow range between -4‰ and +1‰, very similar to the bulk silicate Earth value. In contrast, diverse compositions from -19.7‰ to +13.7‰ were observed for MAG. These differences are likely pre-accretionary in origin and potentially point towards isotopically distinct precursors. If Earth accreted from enstatite-chondrite-like material, carbon potentially hosted by Earth's core may have an isotopically light signature when compared to the mantle. Although graphite-bearing clasts in unequilibrated ordinary chondrites (UOCs) are extraordinarily rare, these clasts are of particular interest as they might represent materials, not corresponding to known meteorites. Graphite from these clasts show coinciding carbon-compositions with a mean δ13C close to -1‰. Although the coinciding compositions might argue for a genetic relationship among the clasts, petrographic evidence suggests they have experienced distinct thermal histories.